Efficacy and Safety of Fruquintinib Plus PD-1 Inhibitors Versus Regorafenib Plus PD-1 Inhibitors in Refractory Microsatellite Stable Metastatic Colorectal Cancer - Sun, Liying; Huang, Shenglan; Li, Dan; Mao, Ye; Wang, Yurou; Wu, Jianbing (Frontiers in Oncology, 2021)
Background: Metastatic colorectal cancer (mCRC) with microsatellite stability (MSS) or mismatch repair proficient (pMMR) is resistant to immune checkpoint inhibitors. Studies have shown that antiangiogenic drugs combined with PD-1 inhibitors can improve immunosuppression. The purpose of this study was to compare the efficacy of fruquintinib combined with PD-1 inhibitor (FP) and regorafenib combined with PD-1 inhibitor (RP) in the treatment of advanced mCRC with MSS or pMMR. Materials and methods: We retrospectively collected advanced MSS or pMMR metastatic colorectal cancer patients from the second affiliated Hospital of Nanchang, China, from June 2019 to March 2021. Then analyzed and compared the efficacy and safety of FP and RP. Results: A total of 51 patients who met the criteria were divided into FP group (n = 28) and RP group (n = 23). The overall response rate of the two groups was (7.1 vs 8.7%), and the disease control rate was (89.3 vs 56.5%). The median progression-free survival time were higher in the FP group than in the RP group (6.4months vs 3.9months, respectively; p = 0.0209). No liver metastasis, KRAS wild type and left colon tumor may be the beneficiaries of FP. 8 patients (15.7%) had grade 3 toxicity related to treatment. Cox multivariate regression analysis showed that the treatment method was independent risk factors for median progression-free survival time. Conclusion: Our study indicated that FP could improve progression-free survival time of patients with advanced mCRC compared with RP.